The Influence Of Marketing Mix (7Ps) On Purchasing Decisions At Estusae Café Trawas - Mojokerto - Retno Dewi Safitri; Rahayu Rahayu; M. Syamsul Hidayat (Student Scientific Creativity Journal, 2023)
Competition in the culinary industry presents numerous challenges that influence a competitor's standard. As these factors impact consumer decisions, a comprehensive marketing approach is required to maintain market share and overcome competition. The purpose of this study is to investigate the influence of 7P marketing strategy variables (product, price, promotion, place, people, process, physical evidence) on consumer purchasing decisions at Estusae Cafe. A quantitative methodology was employed in this study utilizing purposive sampling. The target population was comprised of all patrons who have consumed products at Estusae Cafe. Data was obtained via questionnaires distributed to respondents selected via purposive sampling. To assess the correlation between 7P marketing strategy variables and consumer purchasing decisions, quantitative data analysis methods were applied using linear regression techniques. The results obtained (F-value of 24.221) from Table 2.10 confirm acceptance of Ha, indicating that all seven independent variables (7P) jointly or simultaneously influence the dependent variable, Estusae Cafe Trawas Purchasing Decision. Additionally, the correlation coefficient (R Square) is 0.648, suggesting that collectively, the 7P variables influence 65% of Estusae Cafe Trawas' Purchasing Decision. The research has revealed that the 7P marketing strategy holds significant importance in influencing consumer purchasing behavior. Such findings carry broader academic implications.